Is catheterization via distal transradial access feasible in children? From vessel diameter perspective - Zhao, Yidong; Chen, Tao; Yang, Ling; Mao, Wenjie; Wan, Yu; Zhang, Liwen; Ding, Heng; Cai, Gaojun; Huang, Zhiying (Frontiers in Cardiovascular Medicine, 2024)
Background: Distal radial artery (DRA) access is an infrequent alternative access for pediatric catheterization. The feasibility of using the DRA for arterial catheterization in children depends on the vessel's size.Objectives: This study aims to provide a reference for pediatric catheterization via DRA access by evaluating the diameter of the DRA in the anatomic snuffbox (AS).We conducted a retrospective review of clinical and vascular ultrasound data of 412 children (ages 3 to 12) who were scheduled for arterial blood gas analysis via the DRA due to serious respiratory diseases between June 2023 and October 2023.The corrected DRA diameter in the AS was 1.97 ± 0.37 mm overall, with no significant difference between males (1.98 ± 0.38 mm) and females (1.95 ± 0.35 mm) (p = 0.457). The anteroposterior, transverse, and corrected DRA diameters increased significantly with age (p< 0.05). The DRA diameter was significantly smaller than the proximal radial artery (PRA) diameter (1.97 ± 0.37 mm vs. 2.05 ± 0.33 mm, p < 0.001) but larger than the ulnar artery (UA) diameter (1.97 ± 0.37 mm vs. 1.88 ± 0.33 mm, p < 0.001). The proportions of patients with a DRA diameter greater than 2.0 mm and 1.5 mm were 38.83% and 86.89%, respectively. The proportions of patients with DRA diameters > 2.0 mm and > 1.5 mm increased significantly with age (p < 0.01). The percentages of individuals with a DRA/PRA ratio ≥ 1.0 were 55.10% overall, 52.12% in males, and 58.60% in females. DRA diameter showed significant correlations with age (r=0. 275, p<0.01), height (r=0.319, p<0.01), weight (r=0.319, p<0.01), BMI (r=0.241, p<0.01), wrist circumference (r=0.354, p<0.01), PRA diameter (r=0.521, p<0.01), and UA diameter (r=0.272, p<0.01). 3 Conclusion: The DRA diameter in children increases with age and size, making cardiac catheterization is theoretically feasible. Preoperative evaluation of the vessel diameter and intraoperative ultrasound-guided intervention are recommended for paediatric catheterization via the DRA access.